Angiotensin-converting enzyme gene I/D polymorphism and carotid artery disease in renovascular hypertension - Losito, Attilio; Selvi, Antonio; Jeffery, Steve; Afzal, Ali R; Parente, Basso; Cao, Pier Giorgio (American journal of hypertension, 2000)
There is evidence linking the activation of the renin-angiotensin system (RAS) with target organ damage in renovascular hypertension (RVH). A genetic association of the DD genotype of the angiotensin-converting enzyme (ACE) gene with cardiovascular complications has been found in various clinical conditions. The aim of our study was to determine whether the insertion/deletion (I/D) polymorphism of the ACE gene is associated with the high prevalence of target organ damage reported in RVH. A total of 65 atherosclerotic patients (age 68.2 ± 5.2 years) with RVH and 49 atherosclerotic patients (age 68.0 ± 6.3 years) with essential hypertension (EH) were sequentially enrolled when attending the outpatient clinic for specialist assessment of their vascular disorder. Cardiac, renal, and vascular involvement were assessed in both groups and blood was taken for genetic analysis. Patients with RVH had a higher prevalence of left ventricular hypertrophy (LVH), carotid artery disease, and albuminuria than those with EH. In RVH, but not in EH, the DD genotype was significantly associated with severe arterial disease. In RVH, carotid disease (lumen narrowing >60%) was present in 62% of DD patients versus 25% of the other genotypes (OR = 4.90, 95% CI: 1.70–14.13). Such an association was also present in peripheral vascular disease: 72.4% in DD patients versus 41.6% in the other genotypes (OR = 3.67, 95% CI = 1.29–10.36). Logistic regression analysis showed that the DD genotype was the strongest predictor of risk of severe carotid disease. We conclude that, in atherosclerotic RVH, there is an association of the severity of vascular disease with the DD genotype of the ACE gene.